Post-traumatic stress symptoms following sniper attacks: Effects of television viewing and identification with victims - Mash, PhD, Holly B. Herberman; Fullerton, PhD, Carol S.; Ursano, MD, Robert J. (American Journal of Disaster Medicine, 2018)
Objective: A series of sniper attacks in the Washington, DC, area left 10 people dead and three wounded. The authors examined the relationship of sniper-related television (TV) viewing, identification with victims, and peritraumatic dissociation to posttraumatic stress symptoms. Methods: Participants were 1,238 DC residents (ages 18-90, M = 41.7; 51 percent female; 68 percent White) who completed an online survey including items assessing identification, amount of TV, peritraumatic dissociation, and post-traumatic stress symptoms. Identification was measured by assessing to what extent participants identified victims as similar to themselves, a friend, or a family member. Peritraumatic dissociation and post-traumatic stress symptoms were assessed with the Peritraumatic Dissociative Experiences Questionnaire and Impact of Event Scale-Revised. Relationships of TV viewing, identification, and peritraumatic dissociation to post-traumatic stress symptoms were examined by univariable and multivariable regressions and variable interactions. Results: Female gender and higher levels of TV viewing, identification, and peritraumatic dissociation were each related to greater post-traumatic stress symptoms. After adjusting for gender and the predictor variables, higher TV viewing was associated with posttraumatic stress symptoms (B = 0.72, p < 0.01, ΔR2 = 0.05). Participants with greater identification (B = 0.85, p < 0.001, ΔR2 = 0.08) and peritraumatic dissociation (B = 1.58, p < 0.001, ΔR2 = 0.39) reported more post-traumatic stress symptoms. Among those with both high (B = 1.19, p < 0.001) and low TV viewing, identification was associated with post-traumatic stress symptoms. Among those reporting low TV viewing, this association was greater for those who experienced more peritraumatic dissociation (B = −0.09, p < 0.001). Conclusions: Trauma-related TV viewing, which may stimulate identification and peritraumatic dissociation, is an important consideration in understanding development of post-traumatic stress symptoms.